2010
DOI: 10.1016/j.adolescence.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

On being aware and accepting: A one‐year longitudinal study into adolescent well‐being

Abstract: The nature and potential benefit of awareness and experiential acceptance in adolescence remains neglected and understudied. To address this gap in the literature, 776 students (50% female) in Grade 10 completed measures of mindfulness, emotional awareness, and experiential acceptance, as well as measures of major personality traits. To study prospective changes, assessments of emotional well‐being were completed across a 1‐year interval. Analyses revealed that “Acting with Awareness” (engaging fully in one's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 48 publications
5
60
2
1
Order By: Relevance
“…Similarly, mindfulness was positively associated with overall quality of life and negatively associated with internalizing and externalizing problem behaviors in a sample of 5 th through 10 th grade students (Greco, Baer, & Smith, 2011). In a sample of Australian tenth graders from diverse socioeconomic backgrounds, awareness and acceptance, two key components of mindfulness, were associated with lower reported levels of fear, hostility, and sadness, and positively associated with positive affect (Ciarroci, Kashdan, Leeson, Heaven, & Jordan, 2010). The results of these correlational analyses indicated strong support for the positive associations between mindfulness and dimensions of emotional well-being among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mindfulness was positively associated with overall quality of life and negatively associated with internalizing and externalizing problem behaviors in a sample of 5 th through 10 th grade students (Greco, Baer, & Smith, 2011). In a sample of Australian tenth graders from diverse socioeconomic backgrounds, awareness and acceptance, two key components of mindfulness, were associated with lower reported levels of fear, hostility, and sadness, and positively associated with positive affect (Ciarroci, Kashdan, Leeson, Heaven, & Jordan, 2010). The results of these correlational analyses indicated strong support for the positive associations between mindfulness and dimensions of emotional well-being among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Child and Adolescent Mindfulness Measure (CAMM-20) [53] . The CAMM-20 is a 20-item self-report questionnaire that focuses on internal and external awareness as well as mindfulness [53].…”
Section: Methodsmentioning
confidence: 99%
“…The CAMM-20 is a 20-item self-report questionnaire that focuses on internal and external awareness as well as mindfulness [53]. Exploratory factor analysis found support for a CAMM-20 two-factor model of ‘Observing’, noticing and attending to stimuli including internal and external phenomena, and ‘Acting with Awareness (AWA)’ including items that involve absolute focus and engagement with activity in the present moment [53]. The internal consistency of both scales was in the moderate range [53].…”
Section: Methodsmentioning
confidence: 99%
“…Only a few other studies have examined the AFQ-Y or EArelated constructs in relation to psychopathology in youth and all of them have been with adolescents. For example, in nonclinical samples, both sadness and fear in adolescents has been found to be related to their EA (Ciarrochi et al 2011) and their cognitive avoidance (Dickson et al 2012). In a sample of inpatient adolescents, Venta et al (2012) found EA was related to both depressive and anxiety symptoms and disorders.…”
mentioning
confidence: 95%